2021
DOI: 10.1002/hbm.25676
|View full text |Cite
|
Sign up to set email alerts
|

Striatal networks for tinnitus treatment targeting

Abstract: Neuromodulation treatment effect size for bothersome tinnitus may be larger and more predictable by adopting a target selection approach guided by personalized striatal networks or functional connectivity maps. Several corticostriatal mechanisms are likely to play a role in tinnitus, including the dorsal/ventral striatum and the putamen. We examined whether significant tinnitus treatment response by deep brain stimulation (DBS) of the caudate nucleus may be related to striatal network increased functional conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…As core areas of the striatum or striatal network, the lentiform nucleus and caudate (especially the caudate) are crucial in tinnitus perception 34 . When the caudate nucleus is targeted using deep brain stimulation, significant reduction in tinnitus loudness 35 and increased connectivity with the tinnitus network were reportedly observed 36 . Data from an animal model also proved that the caudate‐putamen nucleus plays a sensory gating role in tinnitus 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As core areas of the striatum or striatal network, the lentiform nucleus and caudate (especially the caudate) are crucial in tinnitus perception 34 . When the caudate nucleus is targeted using deep brain stimulation, significant reduction in tinnitus loudness 35 and increased connectivity with the tinnitus network were reportedly observed 36 . Data from an animal model also proved that the caudate‐putamen nucleus plays a sensory gating role in tinnitus 37 …”
Section: Discussionmentioning
confidence: 99%
“…34 When the caudate nucleus is targeted using deep brain stimulation, significant reduction in tinnitus loudness 35 and increased connectivity with the tinnitus network were reportedly observed. 36 Data from an animal model also proved that the caudate-putamen nucleus plays a sensory gating role in tinnitus. 37 The thalamus and hippocampus, as important parts of the limbic system, are closely related to tinnitus generation and are indispensable to the tinnitus frontostriatal gating system.…”
Section: Functional Changes In the Thalamus And Thalamic Subregionsmentioning
confidence: 94%
“…With resting state functional MRI approaches, Gordon et al (Gordon et al 2021) mapped cortical functional connectivity with striatum, finding a putamen cluster that strongly connects functionally to the cortical language network. Hinkley et al (Hinkley et al 2015; Hinkley et al 2021) similarly used functional connectivity to investigate corticostriatal interactions and found ventral striatal connectivity effects in tinnitus participants. A follow up study (Hinkley et al 2021) found that targeted electrical stimulation of the caudal-most caudate tail provided significant benefits to participants with tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Hinkley et al (Hinkley et al 2015; Hinkley et al 2021) similarly used functional connectivity to investigate corticostriatal interactions and found ventral striatal connectivity effects in tinnitus participants. A follow up study (Hinkley et al 2021) found that targeted electrical stimulation of the caudal-most caudate tail provided significant benefits to participants with tinnitus. In children with developmental stuttering, a disorder with both motor and perceptual deficits, decreased functional and structural connectivity with motor, speech, and auditory cortical regions has been observed (Chang and Zhu 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In its chronic phase, tinnitus manifests as a central nervous system disorder. Some prevailing hypotheses include maladaptive neuroplasticity, misappropriated attention, and dysfunctional striatal gating [1]- [3]. While hearing loss association is common, tinnitus severity or distress is often modulated by comorbid anxiety, depression, or mood disturbance.…”
Section: Introductionmentioning
confidence: 99%